Sobre o teorema do valor intermediário - Morais, Fabio Maia de [UNESP] (2013)
In this work we study the Intermediate Value Theorem and we present some applications. This kind of theorem is typical from Calculus in graduation courses. But it is easy to understand and it can be used to solve problems related to topics from high school, for example, to guarantee the existence of solutions for certain equations